Morphological changes and induction of antifungal resistance in Aspergillus fumigatus due to different CO2 levels - Sima Darabian; Sayed Jamal Hashemi; Sadegh Khodavaisy; Somayeh Sharifynia; Mohammad Kord; Maryam Akbari Dana; Farzad Aala; Sassan Rezaie (Mazandaran University of Medical Sciences, 2017)
Background and Purpose: Aspergillosis is one of the most common opportunistic fungal infections in immunocompromised and neutropenic patients. Aspergillus fumigatus (A. fumigatus) is the most common causative agent of this infection. Due to variable CO2 concentrations that pathogens are exposed to during the infection process and to understand the role of CO2, we examined the effects of various CO2 concentrations as one of the environmental factors on morphological changes and induction of antifungal resistance in A. fumigatus. Materials and Methods: A. fumigatus strains were cultured and incubated under 1%, 3%, 5%, and 12% CO2 atmospheres, each time for one, two, and four weeks. The control culture was maintained for one week without CO2 atmosphere. Morphological changes were investigated and antifungal susceptibility test was performed according to the recommendations of the Clinical and Laboratory Standards Institute (CLSI) M38-A2 document. The results of different CO2 atmospheres were compared with that of the control sample. Results: We found that 1%, 3%, 5%, and 12% CO2 atmospheres were associated with morphological colony changes. Macroscopically, the colonies were shallow dark green, smooth, crisp to powdery with reduced growth; microscopic examination revealed the absence of conidiation. The induction of antifungal resistance in the susceptible strains to itraconazole, voriconazole, and amphotericin B increased after exposure to 12% CO2 atmosphere and four weeks of incubation. The MIC values for itraconazole, voriconazole, and amphotericin B were 16 g/ml, 1 g/ml, and 16 g/ml, respectively. These values for the control group were 0.125 g/ml, 0.125 g/ml, and 2 g/ml, respectively. Conclusion: Exposure to different CO2 atmospheres induced morphological changes in A. fumigatus, it seems to increase the MIC values, as well. In parallel, resistance to both itraconazole and voriconazole was also observed.